Thermal vests help patients with anorexia nervosa to cope with mealtime anxiety - Olaia Carrera; Carlos Alvarez; Jose Mazaira; Emilio Gutiérrez (Journal of Eating Disorders)
Abstract Introduction Anxiety around mealtime continuous to hinder nutritional rehabilitation even after significant weight restoration which undermines recovery with pharmacological and psychological treatments proving to be of little effectiveness. This study explored the anxiolytic effects of wearing a warming vest either during lunchtimes or postlunch rest in comparison to treatment as usual in a sample of AN adolescent patients during nutritional rehabilitation. Method 14 consecutive inpatients at a Child and Adolescence Mental Health Unit underwent each of the 3 conditions at lunchtime in random order and separated by 2 days: Treatment as usual, wearing heating vest during lunch time, and wearing heating vest during first 30 min of rest time. Results According to median prelunch anxiety, half of the sample were classified as a High prelunch anxiety group (HPA), while the remaining 7 were classified as a Low prelunch anxiety group (LPA). Wearing the heating vest either during lunch time or during the 30 min lunch rest significantly decreased patient anxiety in the HPA group, but no differences were in observed in the LPA patients. Conclusion These results corroborated prior reports of the anxiolytic effect of warming during lunch rest and extend this anxiolytic effect of warming to lunchtime.